2019
DOI: 10.1021/acs.jpcc.9b05521
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Dependent Growth and Optical Properties of Hybrid Organo-metal Halide Perovskite Magic Sized Clusters

Abstract: Magic sized clusters (MSCs), small nanoparticles with a single size or narrow size distribution, possess unique chemical and physical properties. CH3NH3PbBr3 perovskite MSCs (PMSCs) were synthesized using butylamine (BTYA) and valeric acid (VA) as well as 3,3-diphenylpropylamine (DPPA) and VA as capping ligands in an excess amount. The PMSCs were characterized using UV–vis and photoluminescence (PL) spectroscopy. For BTYA-VA PMSCs, there is an excitonic absorption peak at 424 nm and PL peak at 434 nm, while th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
87
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(95 citation statements)
references
References 34 publications
(61 reference statements)
7
87
0
Order By: Relevance
“…Detail of the MAPbBr 3 -VA-BTYA PMSC synthesis is described in the supporting information (SI). The UV-vis absorption and PL spectra of MAPbBr 3 -VA-BTYA PMSC solution are shown in Figure 1(a) , with the major absorption peak at 424 nm and PL peak at 434 nm, as we reported previously [ 20 ]. Interestingly, these optical peaks decrease in intensity, and simultaneously, a new absorption peak at 402 nm and PL peak at 410 nm appear with intensity increasing over time.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…Detail of the MAPbBr 3 -VA-BTYA PMSC synthesis is described in the supporting information (SI). The UV-vis absorption and PL spectra of MAPbBr 3 -VA-BTYA PMSC solution are shown in Figure 1(a) , with the major absorption peak at 424 nm and PL peak at 434 nm, as we reported previously [ 20 ]. Interestingly, these optical peaks decrease in intensity, and simultaneously, a new absorption peak at 402 nm and PL peak at 410 nm appear with intensity increasing over time.…”
Section: Resultssupporting
confidence: 64%
“…MAPbBr 3 PMSCs with BTYA and VA passivating ligands were synthesized using the reprecipitation method, as described in our previous report [ 20 ]. Detail of the MAPbBr 3 -VA-BTYA PMSC synthesis is described in the supporting information (SI).…”
Section: Resultsmentioning
confidence: 99%
“…The metastability behaviour of PMSCs owing to the abundant charging defects in perovskite surface, including positive-charge defect (i.e., halide ion vacancy) and negative-charge defects (i.e., cation vacancy and PbX 4 2− anti-site defects) 8 . The surface passivation MSCs by various capping ligands, including organic acid and amines have been reported 9 , 10 . It was demonstrated that the PMSCs and PQD structure could be tunning by adjusting the ligand concentration ratio between acid and amines-based ligands implying the crucial role of the ligands to the MSCs formation 9 , 10 .…”
Section: Introductionmentioning
confidence: 99%
“…The surface passivation MSCs by various capping ligands, including organic acid and amines have been reported 9 , 10 . It was demonstrated that the PMSCs and PQD structure could be tunning by adjusting the ligand concentration ratio between acid and amines-based ligands implying the crucial role of the ligands to the MSCs formation 9 , 10 . Unfortunately, the dynamic nature of the interaction between PMSCs surface and capping ligands permits the ligand detachment from the PMSCs surface under various conditions 11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation